Non-Shia practices of Muḥarram in South Asia and the diaspora
1 online resource.
Keywords: "This book analyses engagements with non-Shia practices of Muḥarram celebrations in the past and present, in South Asia and within a larger diaspora. Breaking new ground by bringing together a variety of regional perspectives (Bengal, the Deccan, Pakistan, Trinidad and Tobago, and Singapore) and linguistic backgrounds (Bengali, Bhojpuri, Marathi, Tamil, Telugu, Urdu), the chapters discuss the importance of Muḥarram celebrations in terms of their respective actors. While in some cases, these include an interrelationship with Shia Muslims and their traditions of mourning during Muḥarram, other contributions address contexts in which Shias, and even Muslims, form only a minor component of the celebrations, or even none at all. Focusing on Muḥarram celebrations that are beyond the script provided by Shia Muḥarram practices, this book opens up new perspectives on Muḥarram as a social practice widely shared by South Asians across regions. The book will be a key resource to scholars and students of South Asian Studies, Asian religion, in particular rituals and religious practices, and Islamic Studies but also engaging to non-academic readers interested in the practices of several regions"--